All Nets are Equal, But Some Nets are More Equal Than Others. (1st February 2020) - Rowland, Mark
Much of the dramatic decline in malaria in sub-Saharan Africa since 2000 is due to the massive investment in long-lasting insecticide treated nets (LLIN). According to the latest figures from the World Health Organization (WHO), over half of Africa's population now has access to LLIN, increasing from 33% in 2010 to 57% in 2019 (WHO 2019). In 2018 alone, 197 million LLINs were delivered to Africa by manufacturers. Despite this, LLIN coverage has improved only marginally since 2015. The malaria burden worldwide has fallen only slightly from an estimated 231 million cases of malaria in 2017 to 228 million in 2018, and is at a standstill in Africa. WHO policy is to assess candidate 2nd-in-class products for entomological efficacy only. Due to the significant variation in the specifications of the candidates, to generate the required assurance of comparative performance to 1st in class, WHO has designed a non-inferiority trial design to demonstrate whether each candidate 2nd-in-class test product is no worse in experimental hut trials.